2007
DOI: 10.1892/0891-6640(2007)21[207:bafcep]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Breed Associations for Canine Exocrine Pancreatic Insufficiency

Abstract: An association with EPI in Chows has not previously been reported. In breeds with early-onset EPI, immune-mediated mechanisms are possible or the disease may be congenital. When EPI manifests later, as in CKCS, pathogenesis is likely different (eg, secondary to chronic pancreatitis). Underrepresentation of certain breeds among dogs with EPI has not previously been recognized and may imply the existence of breed-specific mechanisms that protect pancreatic tissue from injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There were a large number of spaniels in the current study, mirroring a pathology study (Watson and others 2007) that found an increased relative risk of pancreatitis in Cavalier King Charles and cocker spaniels, providing further evidence for breed‐related disease in spaniels. Two studies have demonstrated an increased risk of EPI in older Cavalier King Charles spaniels in the UK (Hall and others 1991, Batchelor and others 2007), suggesting that this may be due to CP, although no pancreatic histopathological analysis was performed in those studies. The current study demonstrated histologically confirmed CP in Cavalier King Charles spaniels with EPI and also DM, providing evidence that CP is at least one cause of EPI in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…There were a large number of spaniels in the current study, mirroring a pathology study (Watson and others 2007) that found an increased relative risk of pancreatitis in Cavalier King Charles and cocker spaniels, providing further evidence for breed‐related disease in spaniels. Two studies have demonstrated an increased risk of EPI in older Cavalier King Charles spaniels in the UK (Hall and others 1991, Batchelor and others 2007), suggesting that this may be due to CP, although no pancreatic histopathological analysis was performed in those studies. The current study demonstrated histologically confirmed CP in Cavalier King Charles spaniels with EPI and also DM, providing evidence that CP is at least one cause of EPI in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…Veterinarians requested serum cobalamin analysis more frequently in younger German Shepherd Dogs and Irish Setters, which suggests that, early in life, both breeds are susceptible to gastrointestinal disease. It has been shown in North America and in Europe that EPI in German Shepherd Dogs 2 is a disease that occurs early in life and is suspected to be hereditary. The same applies for the sensitive enteropathy in Irish Setters, but this condition has been reported only in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of Domestic Shorthair is most likely a reflection of the common occurrence of this breed in the households in general and did not identify a breed predisposition. In contrast to this, a breed predisposition for canine EPI was described for German Shepherds, Chows, Cavalier King Charles Spaniels, and Rough-Coated Collies [ 21 ]. Even dog breeds that are underrepresented for EPI were described: Boxers, Golden Retrievers, Labrador Retrievers, Rottweilers, and Weimaraners [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, a breed predisposition for canine EPI was described for German Shepherds, Chows, Cavalier King Charles Spaniels, and Rough-Coated Collies [ 21 ]. Even dog breeds that are underrepresented for EPI were described: Boxers, Golden Retrievers, Labrador Retrievers, Rottweilers, and Weimaraners [ 21 ].…”
Section: Discussionmentioning
confidence: 99%